Plain Radiographic Analysis of Laryngeal Dimensions in Young Children: Normal versus Croup - Youngdae Kim; Ji-Eun Park; Jung-Heon Kim (MDPI AG, 2022)
(1) Background: Contrary to a tenet of the funnel-shaped pediatric larynx with the cricoid level being narrowest, recent studies show the glottis and subglottis as the narrowest levels. To locate the functionally narrowest level of the larynx, we reported normal laryngeal dimensions and their croup-related changes in young children. (2) Methods: We reviewed normal plain neck radiographs recorded for the evaluation of minor trauma or foreign bodies in 504 children aged ≤4 years who visited the emergency department from 2016 through 2021. Using computed tomography-based localization of the glottis, we radiographically defined the subglottis and cricoid. At these levels, we measured diameters and calculated cross-sectional areas (CSAs) on the radiographs. The values were compared to the equivalent values of a 1:1 age-matched population with croup. (3) Results: In the study population (n = 401), the narrowest diameter and CSA were observed in the glottis. In detail, the mean anteroposterior/transverse diameters were 9.8/3.4 mm at the glottis, 8.5/5.6 mm at the subglottis, and 7.4/6.8 mm at the cricoid (p < 0.001), respectively. In the same order, the mean CSAs were 26.5, 38.1, and 40.5 mm2 (p < 0.001). All dimensions were narrower in the croup population (p < 0.001). We found croup-related narrowing, namely reductions in the transverse diameter and CSA that were more severe closer to the glottis (p < 0.001), without differences per level in the anteroposterior diameter. (4) Conclusions: This study confirms the glottis as the narrowest level of the larynx in young children. In addition, level-based differences in croup-related narrowing suggest some point between the glottis and subglottis as the functionally narrowest level.